Movement of understanding of mathematical literacy from Montessori's perspective: an approach to the teaching processes of Geometry - Alves, Luiza Destefani; Mocrosky, Luciane Ferreira; de Oliveira Batista, Josiel; Bicho, José Sávio [UNESP] (My University, 2022)
Background: Mathematical literacy has been thematised in our studies by the importance of the initial ideas of mathematics in school paths. In this investigative path, the phenomenon of mathematics-literacy-from-Montessori-perspective stood out. Objectives: To answer the question: What is this, mathematical literacy from Montessori's perspective? Design: Research of a theoretical nature, with a hermeneutic study of three works by Montessori closest to the phenomenon: The Discovery of the Child, Psychoarithmetic and Psychogeometry. After successive readings, we highlighted in each work excerpts that approached the question, calling them Units of Meaning (UM). Each UM was interpreted in dialogue with the work itself and other relevant authors. In all, 84 UMs were evidenced, which converged to 15 core ideas (CI). Placing all these CI side by side and asking what they said in the light of the guiding question, they enabled new convergence movements, evidencing basic characteristics of the phenomenon and geometry revealed itself as one of the guiding threads of mathematics teaching that aims at students' learning. Setting and Participants: The theoretical study analysed the three works mentioned above. Data collection and analysis: The works that were closest to the highlighted phenomenon were selected and analysed hermeneutically. Results: The movement of understanding geometry, emerging from a larger study, clarifies Montessori's understanding of the arithmetic-algebra-geometry triad, with a strong appeal to sensations and perception, emphasising the use of manipulative material, and with sequences that privilege abstractions. Conclusion: Knowing Montessori's pedagogical proposal favours expanding teaching knowledge about mathematical literacy, woven in the close connection between methodologies, manipulative materials, articulation of mathematics, and teaching posture.
Movimento de compreensão da alfabetização matemática na perspectiva de Montessori: uma abordagem para os processos de ensino da geometria
Keywords: Geometry; Mathematical literacy; Montessori; Teacher training